Penggunaan Akun TikTok @beautetox dalam Membangun Brand Image Scrub Tanpa Bilas Pertama di Indonesia - Maria Patricia Sitorus; Heni Hayat (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The rapid growth of TikTok as a digital communication platform has encouraged beauty brands to utilize social media to build brand image and strengthen audience engagement. Beautetox, a local beauty brand, uses the TikTok account @beautetox to introduce its no-rinse scrub product through educational and interactive content. This study aims to analyze how the TikTok account @beautetox is used to build the brand image of no-rinse scrub products in Indonesia. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews with five active followers of the TikTok account @beautetox, content observation during January–March 2025, and documentation studies. The analysis used Social Information Processing (SIP) theory and Chris Heuer's 4C concept (context, communication, collaboration, and connection). The findings show that informative product demonstrations, audience interaction through comments, and user testimonial content play an important role in shaping positive audience perceptions. Beautetox is perceived as a practical beauty brand with a distinctive product identity. The study concludes that TikTok can function as an effective communication medium in building brand image within the beauty industry.